UI/UX Design of a Mobile-Based English Tutoring LMS Application Using the Double Diamond Method - Afrida Lailiyah Hanim; Abdul Rezha Efrat; Prasasti Karunia Farista (bit-Tech, 2025)
Digital learning platforms have become increasingly important in supporting the teaching and learning process, including in English tutoring services. However, the platform currently used by Madani English House still faces several challenges, such as the absence of gamification features, limited progress tracking, and insufficient learning management capabilities. These limitations reduce student engagement and hinder effective monitoring of learning outcomes. This study aims to design the UI/UX of a mobile-based Learning Management System (LMS) specifically for English tutoring at Madani English House using the Double Diamond approach. This method was selected for its structured and iterative nature, which enables in-depth understanding of user needs and continuous refinement of the design. Through its four phases—Discover, Define, Develop, and Deliver—the Double Diamond approach guided the process from identifying user pain points to translating them into targeted design solutions that directly address the limitations of the existing system. Data collection methods included interviews with students, development of empathy maps, and creation of user personas, which revealed key user expectations such as interactive features, visual clarity, and performance tracking. These insights informed the design of gamified elements, intuitive navigation, and clear progress indicators tailored to enhance both engagement and learning outcomes. Usability evaluation was conducted using the System Usability Scale (SUS), resulting in a score of 88.5, categorized as “Excellent.” This demonstrates that the Double Diamond method effectively contributed to a user-centered LMS design that is functional, engaging, and aligned with the needs of the English tutoring context at Madani English House.